Preparation of an Asymmetric Membrane from Sugarcane Bagasse Using DMSO as Green Solvent - Dang Thi To Nu; Nguyen Phi Hung; Cao Van Hoang; Bart Van der Bruggen (My University, 2019)
Preparation of an Asymmetric Membrane from Sugarcane Bagasse Using DMSO as Green Solvent
Keywords: Asymmetric Membrane; Sugarcane Bagasse; Green Solvent